Endocannabinoid Hydrolase Inhibitors: Potential Novel Anxiolytic Drugs - Zhao H; Liu Y; Cai N; Liao X; Tang L; Wang Y (Dove Medical Press, 2024)
Hongqing Zhao,1,2,* Yang Liu,1,2,* Na Cai,3 Xiaolin Liao,1,2 Lin Tang,2,4 Yuhong Wang1,2 1Science & Technology Innovation Center, Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of China; 2Hunan Key Laboratory of Traditional Chinese Medicine Prevention & Treatment of Depressive Diseases, Changsha, Hunan, People's Republic of China; 3Outpatient Department, the First Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of China; 4Department of Pharmacy, the First Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of China*These authors contributed equally to this workCorrespondence: Lin Tang; Yuhong Wang, Email tanglin0018@163.com; wangyh107@126.comAbstract: Over the past decade, the idea of targeting the endocannabinoid system to treat anxiety disorders has received increasing attention. Previous studies focused more on developing cannabinoid receptor agonists or supplementing exogenous cannabinoids, which are prone to various adverse effects due to their strong pharmacological activity and poor receptor selectivity, limiting their application in clinical research. Endocannabinoid hydrolase inhibitors are considered to be the most promising development strategies for the treatment of anxiety disorders. More recent efforts have emphasized that inhibition of two major endogenous cannabinoid hydrolases, monoacylglycerol lipase (MAGL) and fatty acid amide hydrolase (FAAH), indirectly activates cannabinoid receptors by increasing endogenous cannabinoid levels in the synaptic gap, circumventing receptor desensitization resulting from direct enhancement of endogenous cannabinoid signaling. In this review, we comprehensively summarize the anxiolytic effects of MAGL and FAAH inhibitors and their potential pharmacological mechanisms, highlight reported novel inhibitors or natural products, and provide an outlook on future directions in this field.Keywords: endocannabinoid hydrolase inhibitors, endocannabinoid system, anxiety disorders, anxiolytic, MAGL, FAAH